Visual accessibility of wayfinding signage in campus library for internationl student (ARTEKS : Jurnal Teknik Arsitektur, 2022)
A campus library is an educational environment that has a wide range of academic activities that are organized and arranged according to hierarchy and activity requirements. When activity in the campus library increases, so does the intensity of a movement that does not correspond to the availability of compelling and wayfinding signage within the library. In fact, on campus there must be international students who are not fluent in speaking and reading the local language. The purpose of the study is to investigate a wayfinding signage issue in interpreting the information through visual graphic for international student in campus library. In this issue, it will examine the importance of visual graphic design used in wayfinding signage for interpreting information and determined the require component which help the topic incorporate a greater user experience through visual qualities such as graphic, text, color and size. Therefore, the (TWO) 2 objectives of this research paper are 1) To identify the current graphic design of the wayfinding signage in the campus library and 2) To determine the graphic design in interpreting information in the wayfinding signage. It will use a qualitative method by John Creswell in collecting the data at several proposed case studies place.
Keywords: Campus library; Cultural difference; Graphic design; Wayfinding signage